True rise in anaphylaxis incidence: Epidemiologic study based on a national health insurance database. Issue 5 (February 2017) - Yang, Min-Suk; Kim, Ju-Young; Kim, Byung-Keun; Park, Heung-Woo; Cho, Sang-Heon; Min, Kyung-Up; Kang, Hye-Ryun
Abstract : Abstract: The incidence trend of anaphylaxis in Asia is not well investigated. The aim of this study is to estimate the entire population-based incidence of anaphylaxis in Korea using a nationwide administrative database. Data over a 7-year period (2008–2014) was obtained from the Korean National Health Insurance (NHI) claims database which covers 97.9% of the entire Korean population. Using diagnosis codes from the International Classification of Diseases-10 for anaphylaxis (T78.0, T78.2, T80.5, and T88.6), we identified the annual number of patients who had visited any hospital with a primary diagnosis of anaphylaxis. Incidence rates were calculated using the population distribution data of all NHI beneficiaries. The incidence of anaphylaxis in Korea was 32.19 episodes per 100, 000 person-years in 2014, which nearly doubled from 2008 (16.02 episodes per 100, 000 person-years). The incidence of anaphylaxis increased continuously throughout these years regardless of gender and age groups ( P for trend < 0.001). Female was significantly less predisposed than male (adjusted odds ratio [OR], 0.69; 95% confident interval [CI], 0.66–0.72; P < 0.001). The incidence was the lowest in 0 to 19 age group and the highest in 40 to 69 age group (adjusted OR, 2.41; 95% CI, 2.29–2.54; P < 0.001). In conclusion, we report the increasing time trend of anaphylaxis incidence rates using nationwide claims database for the first time in Asia.